83.8k views
0 votes
6x - 2 = 22 need help

1 Answer

3 votes

Given the equation:


6x-2=22

to find the value of 'x', first we need to move the constant -2 to the other side of the equation. By doing so, the constant will change its sign (since it's substracting), so we would get the following:


\begin{gathered} 6x-2=22 \\ \Rightarrow6x=22+2=24 \\ \Rightarrow6x=24 \end{gathered}

Next, to remove the coefficient of the term 6x, we have to move the 6 to the right side dividing (since it's multiplying the variable x) to get the following:


\begin{gathered} 6x=24 \\ \Rightarrow x=(24)/(6)=4 \\ x=4 \end{gathered}

therefore, x = 4

User Kryptic
by
5.3k points